Catching up in economic transition: Innovation in the People's Republic of China and India - Peilei Fan (Asian Development Bank Institute (ADBI), 2018)
In this paper, I examined how the People's Republic of China (PRC) and India, two largest transitional economies in Asia, have engaged in improving their innovation capability in the economic transition. First, I measured and compared innovation capability of both countries by using not only various input and output indicators of innovation systems but also the contribution of technological progress to economic development at different periods of their economic transition. Then I compared how both countries developed their innovation capabilities by focusing on their transformation of the national innovation systems since the economic reform and evolving technology policies. Furthermore, I provided a brief view on how the emerging innovative cities in both countries became dominated the innovation activities of their respective countries.
Keywords: O31; O3; L65; 330; innovation; R&D; the People's Republic of China; India